A Perspective on the Educational Psychological Value of Jurassic Park and Similar Films for Bioethics Discussions - Attwood, Adam I. (Frontiers in Education, 2021)
This commentary paper, with recommendations for teachers and teacher educators, discusses the Jurassic Park science-fiction series with a parallel mention of the Night at the Museum trilogy addressing the educational value of this subgenre of film for bioethics discussion in social studies classes. These film series were selected for analysis because of their long-standing popularity, especially Jurassic Park that has continued as a series for over three decades. As such, this commentary posits that representations of anthropology, archaeozoology, and related fields in popular entertainment films can be motivational for students to explore these careers for themselves or at least develop an interest in studying bioethics as an important discussion in individual and community rights.